Analisis Peran Bendahara Sekolah dalam Manajemen Keuangan dan Pembiayaan Sekolah di MTSS YP Al-Azhar Medan Sunggal - Samni, Atika Sania; Saputri, Dea; aulia hasibuan, Lawri; Br Hombing, Wanti; Amalia, Nadra (eScience Humanity Journal, 2025)
This research is motivated by the phenomenon of school financial management that demands transparency, accountability, and compliance with regulations. However, in many schools, obstacles such as manual recording, limited administrative human resources, and minimal training are still found, resulting in less than optimal fund management. This study aims to analyze the role of the treasurer in school financial management, including budget planning, fund management implementation, bookkeeping processes, transparency, obstacles, and improvement strategies at MTsS YP Al-Azhar Medan Sunggal. The subject of the study was the school treasurer, while the object of the study was the practice of school financial management that takes place within the MTsS YP Al-Azhar administration environment. The study used a descriptive qualitative approach with data collection techniques in the form of direct observation and in-depth interviews with the school treasurer as the main informant. The results of the study indicate that the treasurer plays an important role in preparing the RKAS-based budget, managing income and expenditures, preparing routine financial reports, and ensuring accountability through transaction evidence and periodic audits. However, several obstacles were found, such as limited digital administration capabilities, rapid regulatory changes, and less than optimal guidance from the agency. Improvement strategies include routine record-keeping, sector-based reporting, budget efficiency, and intensive coordination with the principal. This study concluded that the treasurer's role significantly determines the effectiveness of school financial management and directly impacts operational smoothness and the quality of educational services.